Lifetime cigarette smoking and later‐life brain health: The population‐based 1946 British Birth Cohort: Public health: ADRD risk and protective factors: Brain changes and mechanisms. (7th December 2020) - James, Sarah‐Naomi; Lane, Christopher A; Parker, Thomas D; Keshavan, Ashvini; Buchanan, Sarah M; Keuss, Sarah E; Cash, David M; Malone, Ian B; Barnes, Jo; Sudre, Carole H; Coath, William; Prosser, Lloyd; et al.
Abstract: Background: Cigarette smoking is implicated as a risk factor for dementia, but the underlying mechanisms are poorly understood. In a population‐based sample free of dementia, we examine associations between smoking patterns over the life course and imaging markers associated with dementia. Method: Dementia‐free participants from Insight 46 (n=458, 49% female, age 69‐71), a sub‐study of the 1946 British Birth Cohort, underwent 18 F‐florbetapir Aβ‐PET and multi‐modal MR imaging including T1, T2, FLAIR and multi‐shell diffusion‐weighted sequences. Information on smoking frequency and cessation (current/former/never) were obtained at multiple timepoints, spanning ages 15‐69 years. Pack‐years were calculated as number of cigarettes smoked/day divided by 20, multiplied by years of smoking. Age and sex adjusted regression analyses examined relationships between smoking metrics and later‐life imaging measures; including Aβ‐PET status, brain, hippocampal and white matter hyperintensity (WMH) volumes, normal appearing white matter (NAWM) fractional anisotropy (FA), mean diffusivity (MD), neurite density index (NDI) and orientation dispersion index (ODI), and Alzheimer's disease (AD)‐related cortical thickness. Result: Increased smoking pack‐years was associated with alterations in NAWM microstructure metrics (lower FA and NDI; higher MD and ODI) and smaller brain and hippocampal volume (Figure 1). There was no significant relationship with Aβ‐PET status (OR=0.99 [95% CI 0.97, 1.01]), WMH volume or AD‐related cortical thickness (Figure 1). Unlike current smokers (n=16, 3%), former smokers (n=285, 61%) had comparable NAWM microstructure metrics to those who had never smoked (n=163, 35%). Conclusion: In a population‐based sample without dementia or other major neurological problems, increased smoking frequency and duration over 50 years was associated with altered white matter microstructural metrics, and smaller brain and hippocampal volumes. However, there was no evidence that smoking was associated with markers of AD pathology (amyloid‐PET, AD‐related cortical thickness) or cerebral small vessel disease (WMH). Former smokers were comparable to non‐smokers on measures of microstructural metrics, suggesting that smoking‐related microstructural changes may at least partly be reversible. Stopping or reducing smoking may help reduce risks to brain health via microstructural pathways.